INTERNAL LOCUS OF CONTROL SEBAGAI MODERASI PADA PENGARUH KOMPETENSI DOSEN TERHADAP TINGKAT PEMAHAMAN AKUNTANSI (Studi Empiris pada Mahasiswa Program Studi Akuntansi di Fakultas Ekonomi Universitas Slamet Riyadi Surakarta) - Harimurti, Fadjar -; -, Rispantyo - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2014)
ABSTRACT This study aimed to find empirical evidence the effect of lectures competence to level of understanding of accounting students, and to analyzing effect lectures competence to level of understanding of accounting students with internal locus of control as moderation variable. The population of this research is all accounting students at the college in UNISRI Surakarta, sample taken of students who pass take courses introduction of accounting, intermediate, and advanced financial accounting. In this research amount of sample are 58 student, sampling method using purposive. To test this hypothesis, researchers used regression analysis and absolute residual-test, while for data processing using SPSS Release 14. The results showed that lectures competence had significant effect on to level of understanding of accounting students, thus H1 is supported. Internal locus of control moderates the effect of lectures competence to level of understanding of accounting students, thus H2 is supported. Keywords: lectures competence, internal locus of control, level of understanding of accounting students.